Observations of total ozone amounts and lower stratospheric temperatures during a stratospheric sudden warming in the Antarctic by TOVS of NOAA-7 - Suzuki, Kazuya; Yamanouchi, Takashi; Yoshino, Takeo; Kawaguchi, Sadao (1985)
P(論文) A comparison of total ozone amounts and lower stratospheric temperature during the 1982 stratospheric sudden warming in the Antarctic is made by the TIROS Operational Vertical Sounder (TOVS) data of NOAA-7 received at Syowa Station. A method assuming a vertical ozone profile is applied to obtain total ozone amounts. The total ozone can be determined independently of the surface measurements. A good agreement between the total ozone amounts derived from satellite data and those of Dobson measurements is seen at Syowa Station. RMS error is 12 DU ((10)^<-3>・atm・cm). A good correlation between the total ozone and the lower stratospheric temperature is observed in the Antarctic. Patterns similar to the wave number 5 structure of the total ozone during the Southern Hemisphere summer are seen during the 1982 sudden warming. departmental bulletin paper